Suboptimal management of severe menopausal symptoms by Nigerian Gynaecologists: a call for mandatory continuing medical education for physicians - Nkwo Peter O (BMC, 2009)
Abstract Background Effective management of menopause is an important way to improve the quality of life of the increasing number of older women. The study sought to find out if Nigerian Gynaecologists offer effective treatment for severe menopausal symptoms. Methods 126 Nigerian Gynaecologists representing the six health zones of Nigeria were interviewed to determine the menopausal symptoms they had ever encountered in their practices, frequency of the symptoms, treatments ever offered for severe symptoms including their attitude to, and practice of hormone replacement therapy. Results A Nigerian Gynaecologist encountered an average of one patient with menopausal symptoms every three months (range: 0-3 patients per month). The commoner symptoms they encountered were hot flushes (88%), insomnia (75.4%), depression (58.0%), irritability (56.3%), night sweats (55.6%) and muscle pains (54.8%) while urinary symptoms (16.7%) and fracture (1.6%) were less common. Treatments ever offered for severe symptoms were reassurance (90.5%), anxiolytics (68.3%), analgesics (14.3), HRT (7.9%), Vitamins (4%), Beta-blockers (3.2%) and Danazol (2.4%). These treatments were offered as a matter of institutional traditions rather than being based on any evidence of their efficacy. Conclusion The result revealed that most Nigerian Gynaecologists prefer reassurance and anxiolytics for managing severe menopausal symptoms instead of evidence-based effective therapies. A policy of mandatory continuing medical education for Nigerian physicians is recommended to ensure evidence-based management of gynaecological problems, including menopause.